Opening of Graves in the Cemetery of the Wielbark Culture in Kowalewko. A Preliminary Analysis - Kalina Skóra (Fasciculi Archaeologiae Historicae, 2017)
The paper discusses a practice of opening of graves which were recorded in the Wielbark Culture cemetery in Kowalewko. Proposals of interpretation which have been suggested so far were discussed and a new approach to the issue was put forward. It was debated to what extent archaeology would be able to answer a question of who and when disturbed graves. Furthermore, potential reasons behind the removal of artefacts which were deposited into the grave in the course of funeral rites were pointed out. This issue still requires further studies and a comparison against a broader cultural background.